Seepage Deformation and Failure of Rock Mass Under High Water Pressure With a Discrete Element Method - Shi, Chong; Zhang, Wenhao; Chen, Xiao; Wang, Lerong (Frontiers in Physics, 2022)
The seepage failure induced by high water pressure along the fault structural plane is one of the main factors for the deformation and failure of underground caverns. Based on the pipe domain seepage model with the discrete element particle flow method, the law of flow conservation is introduced, and the pressure renewal equation is improved by connecting the change of mechanical volume in timestep with the effective stress. The model for pipe domain seepage analysis of fractured rock mass is established, and the sample seepage model is used to simulate and verify the seepage process. Then seepage failure induced by water pressure in an underground tunnel is analyzed by using this model. The results show that the improved pipe domain seepage model conforms to the Darcy's law, the seepage velocity of the model can be changed by controlling the viscosity coefficient, and the tunnel failure phenomenon is consistent with the actual phenomenon in the practical project. The research results can provide a theoretical basis and method for investigating deformation and failure of underground caverns under complex seepage.